An analysis of the current backlash of economic globalization in a model with heterogeneous agents. (2nd September 2020) - Della Posta, Pompeo
Abstract: This paper analyzes the current phase of backlash of economic globalization using a target zone approach in an environment populated by heterogeneous agents. The target zone analysis suggests that there may be a positive expectation effect (a 'honeymoon') when the social costs are credibly expected to remain below the benefits arising from globalization. In such a situation, the latter proceeds even beyond the level that society would be willing to accept in the absence of a such a target. When the costs are expected to exceed the benefits, instead, the opposite phenomenon (a 'divorce') arises. While in the case of exchange rates or interest rates, the passage from 'honeymoon' to 'divorce' might well occur with a discrete jump of the respective variable, rather than gradually, this is not the case when considering economic and social costs. Graduality is obtained thanks to the introduction of the hypothesis of heterogeneous agents. The proportion of those who think that the costs of globalization exceed the benefits increases with globalization and the 'honeymoon'', then, gradually turns into a 'divorce'. Government's redistributive intervention to compensate the losers, however, could reduce the costs of globalization, thereby delaying or even preventing its crisis.